Evaluación de la gametogénesis y fecundidad de corales escleractinios : Orbicella annularis, Pseudodiploria strigosa y Siderastrea siderea, en Isla Fuerte (Boliivar), Colombia (2016)
ABSTRACT: The number of studies on coral reproduction has increased worldwide; nevertheless, in Colombia only few studies have been conducted, and none from the area of the present study. Colonies of the scleractinian coral species Orbicella annularis, Pseudodiploria strigosa, and Siderastrea siderea were sampled in Isla Fuerte (Bolívar), Colombia, in order to evaluate their gametogenesis and fecundity. Samples were taken from the center and the edge of 3-5 colonies of each species between August and September 2011, and between April and June 2012. Samples were xed in 10% formaldehyde solution; later, they were decalci ed using 10% HCl. Finally, they were conserved in 70% ethanol. Fecundity was calculated by direct observation, and the different stages of development were identi ed with histological techniques using Toluidin blue stain. Oocytes or spermaries were not found in any samples during stage I. Oocytes from O. annularis were found during July (stages II and III), and August (II-IV), whereas, oocytes from P. strigosa were found during April (II), and July (II-IV). Oocytes from S. siderea were found in all samples. Spermaries from O. annularis were found only during August. Spermaries from P. strigosa were found during April (II and III), and July (II-IV); and from S. siderea during August (II-IV), and September (II-V). O. annularis presented 394,6 oocyte/cm2 in the center and 20,1 oocyte/cm2 in the edge during July; whereas P. strigosa presented 368,8 oocyte/cm2 in the center during April. In spite of the differences in oocytes between the center and edge of the colonies, in this study the values found were higher than those for other Colombian Caribbean reefs under degradation conditions, such as other sites where fecundity was between 11 and 100 oocyte/ cm2, respectively. These results allow us to observe and conclude that this reef is in better condition compared to two other Caribbean reefs studied. We recommend an annual monitoring of these and other scleractinian coral species in the Colombian Caribbean.